ANALYSIS OF MANAGEMENT OF MULTICULTURAL EDUCATION IN ELEMENTARY SCHOOLS - Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2022)
This study focuses on the subjects, a group of 4 people made up of the school principal, 3 high-class instructors, and tries to assess the management of primary school education that is focused on multicultural education in elementary schools. According to the findings of interviews conducted using a Google Form with informants who have knowledge and experience regarding the incident, the researcher used a qualitative approach through a descriptive method in this study. This method aims to explain a piece of data, an event, or an event that is explored based on the results of the interviews. A structured and occurs with existing justice research approach known as the descriptive method describes or explains data based on facts in terms of objects. Techniques for gathering data that are based on the findings of interviews, observations, and documentation. The results of this study suggest that administration of primary school instruction involves planning, as seen by the creation of teaching tools that are multiculturally integrated. a managerial structure that is built on a multicultural outlook These four aspects are seen based on multicultural values, namely equality, fairness, democracy, freedom, and tolerance, as can be seen from the various activities carried out by the school. The implementation is seen based on the process of implementing teaching and learning activities and supervision, which includes periodic monitoring carried out. According to the study's findings, planning is involved in managing the elementary school curriculum as shown through the creation of multicultural teaching materials.